2005
DOI: 10.1007/s00436-005-0090-y
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine expression in CD4+ cells exposed to the monocyte locomotion inhibitory factor produced by Entamoeba histolytica

Abstract: Entamoeba histolytica produces monocyte locomotion inhibitory factor (MLIF), a pentapeptide with in vitro and in vivo anti-inflammatory properties. MLIF may interfere with leukocyte migration, disturbing the balance of pro- and anti-inflammatory cytokines secreted by CD4(+) T lymphocytes. We evaluated the effect of MLIF on expression of pro- and anti-inflammatory cytokines in human CD4(+) T lymphocytes. Regulatory cytokines [interleukin-1 beta (IL-1beta), IL-2, interferon gamma (IFN-gamma), IL-5, IL-6, and IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…During the pathological process after the onset of ischemia, the expressions of adhesion molecules including ICAM-1 and VCAM-1 were increased greatly, which mediates a pivotal role in ischemic injury by promoting leukocytes adhering to the vascular endothelium and crucially aggravating the inflammatory response. 22 It is reported that anti-ICAM-1 antibody reduces ischemic damage in the transient MCAO rat. 23 As expected, the data first validated our hypothesis that MLIF can protect brain injury in cerebrovascular ischemia by an anti-inflammatory role with antagonism on ICAM-1/ VCAM-1 expressions.…”
Section: Discussionmentioning
confidence: 98%
“…During the pathological process after the onset of ischemia, the expressions of adhesion molecules including ICAM-1 and VCAM-1 were increased greatly, which mediates a pivotal role in ischemic injury by promoting leukocytes adhering to the vascular endothelium and crucially aggravating the inflammatory response. 22 It is reported that anti-ICAM-1 antibody reduces ischemic damage in the transient MCAO rat. 23 As expected, the data first validated our hypothesis that MLIF can protect brain injury in cerebrovascular ischemia by an anti-inflammatory role with antagonism on ICAM-1/ VCAM-1 expressions.…”
Section: Discussionmentioning
confidence: 98%
“…MLIF is a soluble pentapeptide with anti-inflammatory properties, inhibiting the production of NO (42) and pro-inflammatory chemokines (43) by human leukocytes. More recently, MLIF was found to disturb the balance of pro-and antiinflammatory cytokines, specifically, inhibit IL-1 while favor IL-10 production by CD4 + T cells (44).…”
Section: Innate Cell-mediated Immunity To E Histolyticamentioning
confidence: 99%
“…In vitro amebic components have favored Th2 cytokine production, with suppression of the Th1 cytokines (72). The amebic molecules conferring this suppression remain to be determined, but perhaps include MLIF activity (44). The Th1 to Th2 shift during amebic infection might result in a retarded T cell response directed to amebic antigen.…”
Section: T Cell-mediated Immune Response To E Histolyticamentioning
confidence: 99%
“…Previous work studying the effect of MLIF on inflammation, specifically the inhibition of interleukins, such as IL-2, IFN- and IL-1, indicates that MLIF acts selectively in different cell lineages. At least two possible explanations could account for this effect: MLIF may either inhibit soluble pro-inflammatory or regulate apoptosis mediators [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…PP Effect of the Monocyte Locomotion Inhibitory Factor (MLIF) a Natural Anti-Inflammatory Produced by 253 E. histolytica on Apoptosis in Human CD4+ T Lymphocytes phokine chemotactic or lymphocyte-derived chemotactic factor (LDCF), but has no effect on polymorphonuclear neutrophils [12]. MLIF is capable of downregulating some pro-inflammatory cytokines, including IFN-, IL-2, and IL-6, and of inducing the anti-inflammatory cytokines IL-4 and IL-10 [22]. MLIF delays the arrival of mononuclear leukocytes into Rebuck chambers applied to the skin of healthy human volunteers [12].…”
Section: Discussionmentioning
confidence: 99%